Analisis Peran Pemerintah sebagai Salah Satu Aktor Penggerak Ekonomi Kreatif di Sumatera Utara - Sihombing, Josua Adrio; Manalu, Riris Hotma Roito; Manik, Elisabeth Fitryani; Lubis, Putri Kemala Dewi (Masyarakat Ekonomi Syariah Bogor, 2024)
The creative economy plays a vital role in regional economic development, particularly in areas like North Sumatra. This study analyzes the government's role as one of the key actors in driving the creative economy in this region. The research method used is a qualitative descriptive approach with data collection techniques through content analysis and descriptive analysis from various sources such as books, journals, and related research. The results show that the government of North Sumatra has provided significant support through incentives, training, legal protection, and the development of a digital ecosystem for MSMEs and other creative economy sectors. This support is expected to enhance innovation, economic growth, and competitiveness at the regional level. Evaluating the effectiveness of government policies and stakeholder collaborations is crucial to ensure the positive impact of creative economy development efforts in North Sumatra.